Aspek Reproduksi Ikan Tongkol Abu-Abu (Thunnus tonggol) Yang Didaratkan Di Pelabuhan Pendaratan Ikan Kedonganan - Hanif Abdullah; I Wayan Restu; Made Ayu Pratiwi; Gde Raka Angga Kartika (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2020)
Longtail tuna is one of the most important pelagic fish species found in Indo-Pacific waters, living in neritic areas. This study aimed to know about reproduction aspect of Longtail Tuna such as gonado somato index, fecundity and length of first maturity. This research was carried out for 5 months from October 2018 to January 2019. The research was conducted in Kedonganan fish landing port. Data analysis that used was the level of gonad maturity, gonad maturity index, fecundity, sex ratio and length of gonad maturity. Longtail tuna at Kedonganan fish landing port actively reproduce in October 2018. The highest value of maturity index of the gonad in October 2018 at Kedonganan fish landing port, shows that in that month is the peak of spawning season. This is in accordance with the number of fish caught more at the size of gonad maturity level III and IV in that month. Longtail tuna’s fecundity is around 18.000-24.000. Fish sex ratio of male and female is unbalanced. Differences in the number of Male and female is suspected because of differences in fish areas in spawning and foraging. The first length of maturity (Lm) of longtail tuna in the waters of the Kedonganan fish landing port were 488-496 mm fork length.